Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1593/neo.09542
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Actin-Binding Protein Transgelin with Lymph Node Metastasis in Human Colorectal Cancer

Abstract: Metastatic dissemination of primary tumors is responsible for 90% of colorectal cancer (CRC) deaths. The presence of positive lymph nodes, which separates stage I/II from stage III CRC, is a particularly key factor in patient management. Here, we describe results of a quantitative proteomic survey to identify molecular correlates of node status. Laser capture microdissection and two-dimensional difference gel electrophoresis were used to establish expression profiles for 980 discrete protein features in 24 hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 63 publications
6
101
1
Order By: Relevance
“…TMA used in the confirmatory studies represented 94 cases of eligible CRC specimens (14 node-negative, 22 node-positive) and was used for immunohistochemistry with anti-PRDX6 antibody. This TMA contained carcinoma samples in duplicate, with normal control colonic mucosa [16]. Immunostaining was assessed independently by a pathologist in a blinded manner.…”
Section: Tissue Samples and Assessment Of Crc Tissue Microarrays (Tmas)mentioning
confidence: 99%
“…TMA used in the confirmatory studies represented 94 cases of eligible CRC specimens (14 node-negative, 22 node-positive) and was used for immunohistochemistry with anti-PRDX6 antibody. This TMA contained carcinoma samples in duplicate, with normal control colonic mucosa [16]. Immunostaining was assessed independently by a pathologist in a blinded manner.…”
Section: Tissue Samples and Assessment Of Crc Tissue Microarrays (Tmas)mentioning
confidence: 99%
“…Following surgery, the 5-year survival rate of patients with early-stage colorectal cancer is >90%, however, the 5-year survival rate of advanced-stage patients is <10% (6). Although several genes associated with lymph node metastasis have been reported, the molecular mechanisms of early-stage metastasis in colorectal cancer remain unclear (7)(8)(9). Thus, the identification of bio-markers associated with lymph node metastasis of colorectal cancer will benefit clinical evaluation and future treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by this group (56) revealed that activated AKT and c-jun NH2-terminal kinases promote the expression of transgelin in the cytoplasm and contribute to colorectal cancer progression. Additionally, it is revealed that transgelin was located in the cytoplasm and nucleus of colorectal cancer cells (57). Overexpression of transgelin in human colon cancer cells affects the expression of ~250 other transcripts and enhances the metastatic behavior (58).…”
Section: Nuclear Abps In Cancer Cellsmentioning
confidence: 99%